Isotopic and textural evidence for diagenetic fluid mixing in the South Brae oilfield, North Sea - McLaughlin, Órla Marie (University of Glasgow, 1992)
Reservoirs of South Brae Oilfield comprise a 1540m sequence of Upper Jurassic submarine fan sandstones and conglomerates. The diagentic history of the reservoir between 3684 and 4202m was studied using petrographic, geochemical, fluid inclusion thermometry and isotope techniques in core samples from 5 wells. This enabled interpretation of the processes involved in the supply of ions for authigenic mineral growth and allowed the paragenetic sequence and associated porefluid movements to be related to the burial and tectonic history. The earliest diagenetic phase was calcite cementation, which formed concretionary bodies 0.8-4m diameter during shallow burial. These concretions were precipitated from a meteoric fluid 18O= -7%0 SMOW), which flushed through the reservoir during shallow burial, displacing the depositional marine porefluid and causing aggressive dissolution of detrital shell debris, plagioclase (supplying Ca) and K-feldspar. Oxygen isotope values record precipitation at temperatures between 15o and 70oC at depths of 0.3 to 2.3 km. 13C and 87Sr/86Sr ratios record increasing thermal decarboxylation and silicate disolution. No significant diagenetic clays are present, so Al has been lost to the system. This was followed by quartz cementation. Oxygen isotope and fluid inclusion data suggest that the greatest volume of quartz was precipiated at temperatures between 70o and 110o (2.3 to 3.7km), from a layered porewater. Our model suggests that warm, isotopically modified, compaction-driven, basinal waters (18O= + 4 %0 ) overlay cooler meteoric derived waters (18O= -4%0 ). Cementation occurred from 55 to 20Ma and may be related to periods of overpressure release. Silica was supplied locally by presssure solution and possibly from mudrocks. A late dissolution event has enhanced porosity by up to 8%, due to dissolution of diagenetic calcite and K-feldspar, particularly in the upper reservoir zones. This seocndary porosity formation was probably due to the movement of basinal fluids, compacted from the interdigitating Kimmeridge Clay and drained out of the basin laterally through the reservoir. Subsequently, minor amounts of illite, kaolinite, calcite, dolomite and pyrite have further reduced the porosity of South Brae to 3-19%. The oilwater contact has no poroperm effect. From 2Ma, the reservoir sealed and became overpressured by 900psi halting fluid movement through the oilfield, and permitting final hydrocarbon accumulation to occur.